A Unique Specific Jumping Test for Measuring Explosive Power in Basketball Players: Validity and Reliability - Asaf Shalom; Roni Gottlieb; Pedro E. Alcaraz; Julio Calleja-Gonzalez (Applied Sciences, 2023)
The aim of this study was to develop and assess the reliability and validity of an innovative field test that measures lower limb explosive power in basketball players (i.e., alactic anaerobic capacity) for the dominant and non-dominant legs. The test examines the performance of vertical, horizontal, and combined movements while holding the ball—similar to penetration to the basket or layup. Such capabilities are required throughout basketball practice and games, combined with upper and lower body coordination. The study included 22 male basketball players, ages 16–18, members of an elite youth league team in Israel. To assess validity, the participants performed the test for each leg, followed by nine standardized tests that were developed for a range of ball games, including basketball. To assess reliability, the participants performed a retest of the unique test 72-h later. Our findings indicate the validity and reliability of the proposed anaerobic alactic field test for basketball players, for the dominant and non-dominant legs. Moreover, strong correlations were seen between the novel test and the standardized tests, with a high correlation for horizontal explosive power (0.5 < r < 0.7), a very high correlation for vertical explosive power (0.7 < r < 0.9), and a nearly perfect correlation for the two combined (r > 0.9). In conclusion, this unique field test for basketball players could assist coaches in developing and applying optimal training programs and game plans, for players individually, and for the team as a whole. As the test measures each leg separately, it could also offer an assessment tool following players’ injuries.